2020
DOI: 10.1542/hpeds.2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Children With Medical Complexity: The 10-Year Experience of a Single Center

Abstract: Children with medical complexity (CMC) have chronic, multisystem health conditions, substantial health care needs, major functional limitations, and high resource use. They represent ,1% of US children yet account for more than one-third of total pediatric health care costs. Health care systems designed for typical children do not meet the unique needs of CMC. In this special article, we describe the experience of our Comprehensive Care Program for CMC in a pediatric tertiary care center, from its launch in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Several studies have described benefits of care coordination programs for preventing rehospitalization risk among children with medical complexity. In a 10-year review of one care coordination program, Murphy et al 20 found that this program was associated with reduced ED visits, hospital admissions, and total hospital cost. Partners for Kids, an Accountable Care Organization at Nationwide Children’s Hospital in Central Ohio, also demonstrated that care coordination was associated with reduced hospital readmissions, total bed days, and visits to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described benefits of care coordination programs for preventing rehospitalization risk among children with medical complexity. In a 10-year review of one care coordination program, Murphy et al 20 found that this program was associated with reduced ED visits, hospital admissions, and total hospital cost. Partners for Kids, an Accountable Care Organization at Nationwide Children’s Hospital in Central Ohio, also demonstrated that care coordination was associated with reduced hospital readmissions, total bed days, and visits to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not differ from the ones reported by Murphy et al who described a sample of CMC in PPC with a median of fourorgan systems involved. 17 Lower age at symptoms onset is significantly associated with the higher number of medical devices registered.…”
Section: Functional Limitations and Technology Dependencementioning
confidence: 99%
“…Children born extremely prematurely (<27 weeks gestation), for example, typically have complex medical needs and spend the first several months of their critical newborn development hospitalized in the neonatal intensive care unit (NICU) (Nankervis et al, 2010). CMC comprise 1%–3% of the US population (Coller et al, 2016; Murphy et al, 2020; Yu et al, 2021) but account for up to 40% of paediatric hospital expenditures (Berry et al, 2014; Simon et al, 2010). They incur nine times more inpatient visits than children without special healthcare needs (Kuo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%